PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA MODEL PROBLEM BASED LEARNING DENGAN STRATEGI MATHEMATIC HABITS OF MIND - Azkyah Kintan Maharani; Ade Mirza; Dian Ahmad BS (Universitas Tanjungpura, 2021)
AbstractThis research aimed to determine the feasibility of a mathematics learning design based on a problem-based learning model with a mathematic habits of mind strategy on fraction material in junior high school. The feasibility of the learning design was seen from the aspect of validity, practicality, and responsibly from students and teachers. The research used was the Research and Development (R&D) method. The development model used in this study reffered to as the Plomp development model which consists of four stages, including preliminary investigation, design, realization/construction, and test, evaluation and revision. The learning design developed included RPP and LKS. There are five validators involved in validating the learning design. The results of the first validation indicate that the learning design must be revised. After being revised the results were confirmed back to the validator. After being declared valid and practical, then a limited field trial. From the test results, the teacher's response was 84.33% and the student's response was 72.94%. So, the mathematics learning design based on a problem-based learning model with mathematic habits of mind strategy on the fraction material in junior high school was feasible with valid, practical and good response from students and teacher criteria for use.Keywords: Learning Design, Fraction, Problem Based Learning, Mathematic Habits Of Mind